2013
DOI: 10.2337/db12-0365
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Signaling Pathway Effector TCF7L2 Controls Gut and Brain Proglucagon Gene Expression and Glucose Homeostasis

Abstract: The type 2 diabetes risk gene TCF7L2 is the effector of the Wnt signaling pathway. We found previously that in gut endocrine L-cell lines, TCF7L2 controls transcription of the proglucagon gene (gcg), which encodes the incretin hormone glucagon-like peptide-1 (GLP-1). Whereas peripheral GLP-1 stimulates insulin secretion, brain GLP-1 controls energy homeostasis through yet-to-be defined mechanisms. We aim to determine the metabolic effect of a functional knockdown of TCF7L2 by generating transgenic mice that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
106
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 49 publications
3
106
0
1
Order By: Relevance
“…TCF7L2DN has been shown to repress Wnt target gene expression in vitro and in vivo by our team and other investigators (12,(34)(35)(36). The observations that LTCFDN mice exhibit progressive impairment of pyruvate and glucose tolerance along with the upregulation of the gluconeogenic gene program and glucose output in primary hepatocytes indicate that the Wnt signaling cascade negatively regulates hepatic gluconeogenesis.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…TCF7L2DN has been shown to repress Wnt target gene expression in vitro and in vivo by our team and other investigators (12,(34)(35)(36). The observations that LTCFDN mice exhibit progressive impairment of pyruvate and glucose tolerance along with the upregulation of the gluconeogenic gene program and glucose output in primary hepatocytes indicate that the Wnt signaling cascade negatively regulates hepatic gluconeogenesis.…”
mentioning
confidence: 81%
“…Following pivotal studies indicating that the transcription factor 7-like 2 (TCF7L2) is an important risk gene for the development of type 2 diabetes (T2D) (1), great efforts have been made to explore its role as a Wnt signaling molecule in pancreatic b-cells and other tissues including liver (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Although several investigations suggested that TCF7L2 negatively regulates hepatic gluconeogenesis (8,10,11,17), one recent study (7) reported that liver-specific knockout of TCF7L2 reduced hepatic glucose production (HGP), while hepatic overexpression of TCF7L2 increased HGP.…”
mentioning
confidence: 99%
“…The involvement of Wnt signaling in the regulation of glucose metabolism has regained importance in recent years, due to studies in humans in which several components of the Wnt pathway have been identified as risk factors for metabolic diseases, including diabetes mellitus type II and age-related dementia; however, the ultimate effect depends on whether the canonical or non-canonical Wnt pathway is affected (4,14,(53)(54)(55). Furthermore, activation of the Wnt/␤-catenin pathway in vivo promotes a decrease in the plasma glucose level, which modulates the localization and expression of GLUT4 in adipocytes and increases glucose uptake in these cells (56).…”
Section: Wnt Signaling Stimulates Glucose Utilization In Neuronsmentioning
confidence: 99%
“…Although results from these two nonpancreatic tumor-derived cell lines must be interpreted with caution, they stress the need to assess TCF7L2 SNP function in a variety of organs other than pancreas, as it has been shown that TCF7L2 regulates glucose homeostasis through its action in a variety of nonpancreatic tissues such as the liver, 27,28 gut, 29 and brain. 30 Testing the hypothesis of alternative use redundant enhancers in the TCF7L2 gene Testing the hypothesis of person-to-person variation in the use of redundant enhancers in the TCF7L2 gene requires the ability of distinguishing active enhancers from poised/inactive enhancers. Recent work has shown that active enhancers are bi-directionally transcribed resulting in short (o2 kb) noncoding RNAs (enhancer RNAs or eRNAs).…”
Section: Alternative Use Of Redundant Enhancersmentioning
confidence: 99%